Implementasi Model Simulasi dalam Pembelajaran Kosakata Bahasa Arab pada Siswa Kelas V di MIN 1 Bantul Tahun Ajaran 2021/2022 - Amri, Desfiandri Rahmadani; Isnaini, Rohmatun Lukluk (Mahira: Journal of Arabic Studies & Teaching, 2023)
The purpose of this study was to describe the implementation of the simulation model in learning Arabic vocabulary for grade 5 students at MIN 1 Bantul and identify the supporting and inhibiting factors. This study uses descriptive qualitative research methods. Data collection methods consist of interviews, observation, and documentation. The number of informants in this study were 10 people with details of 1 madrasah principal, 1 teacher, and 8 students. The analytical technique used in this research is descriptive qualitative data analysis technique with several stages, namely data reduction, data presentation, conclusion drawing and verification. The data validity technique used credibility test, transferability test, dependability test, and confirmability test. The results of this study indicate that 1) the implementation process of the simulation model in learning Arabic vocabulary for grade 5 students at MIN 1 Bantul consists of initial activities, core activities, and closing activities. The teacher applies a simulation model to each session of learning activities. 2) In its implementation, there are several supporting and inhibiting factors. The supporting factors are a) the skills of teachers who are quite compatible in managing and conditioning the class and skilled in using simulation models in learning by repeating the mufradat taught. b) good enthusiasm of students in following lessons, and c) adequate facilities and infrastructure. The inhibiting factors include a) the teacher is faced with students who still cannot read and write Arabic, and b) students are indifferent when learning. The solutions provided by the madrasa are 1) by holding a special matriculation program for students who cannot read and write Arabic, and 2) trying to maximize the role of teachers and students in order to minimize interference by implementing a simulation model that is packaged in a fun and interesting way for the students.